PENGARUH PENGGUNAAN METODE PROJECT-BASED LEARNING TERHADAP KEMAMPUAN SOSIAL-EMOSIONAL ANAK DI PAUD AL-BARKAH - Neng Kurniasih (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2026)
Project-based Learning (PjBL) method is one of the learning methods that focuses on student-centered learning. This research aims to find out the early childhoods’ social-emotional development aged 5-6 years before and after using the Project-based Learning method at PAUD Al-Barkah, as well as to find out the effect of using the Project-based Learning method on the early childhoods’ social-emotional development aged 5-6 years at PAUD Al-Barkah. This research uses a quantitative method with a pre-experimental design. The results of the study show that based on the t-test results, it is stated that t-count > t-table, 12.860 > 2.086 at a significance level of 0.05, indicating that H0 is rejected and H1 is accepted. Thus, it can be concluded that the use of the Project-based Learning method has a significant effect on the early childhoods’ social-emotional development aged 5-6 years at PAUD Al-Barkah.